The relationship between artificial intelligence and low-skilled employment in South Africa - Fiyinfoluwa Giwa; Nicholas Ngepah (Heliyon)
As artificial intelligence (AI) continues to advance, its impact on employment is a topic of concern. In South Africa, where low-skilled labor forms a significant portion of the workforce, the integration of AI technologies raises questions about the future of employment opportunities and economic stability. This manuscript explores the relationship between AI adoption, low-skilled employment dynamics, and its implications using key economic indicators such as inflation, interest rates, and foreign direct investment (FDI). Employing the Vector Error Correction Model (VECM) approach from 2012Q1 to 2021Q4, the study's findings reveal a significant negative correlation between artificial intelligence and low-skilled employment in the long run. Granger causality tests reveal directional relationships, with AI investment unidirectionally causing low-skilled employment. As a policy implication, this study recommends implementing training programs to equip workers with the necessary skills to adapt to the evolving job market influenced by technological advancements. Additionally, it suggests monitoring the implementation of AI technologies and establishing policies to mitigate labor market disruptions.